Pimachrysa (Neuroptera: Chrysopidae: Nothochrysinae): Larval Description and Support for Generic Relationships - Catherine A. Tauber; David K. Faulkner (Psyche: A Journal of Entomology)
We describe the previously unknown larval characteristics of Pimachrysa (second and third instars), and we provide new comparative data on the Nothochrysa californica Banks larvae that were described earlier. The Pimachrysa larvae (identified as Pimachrysa fusca Adams) express the numerous features that characterize the chrysopid subfamily Nothochrysinae. They resemble Hypochrysa larvae in many respects, but several differences support retaining the two genera as separate. It now appears that the reputedly more archaic, small bodied, nothochrysine genera (e.g., Dictyochrysa, Hypochrysa, and Pimachrysa) have naked larvae that differ distinctly from the larvae of Nothochrysa species, all of which are debris-carriers. In addition, the pattern of variability in Nothochrysa larval features supports the proposal that this genus has a closer relationship with the other chrysopid subfamilies than do the small-bodied nothochrysine genera. The findings are consistent with the hypothesis that larval nakedness (as opposed to debris-carrying) was the ancestral life style for the extant chrysopid clade.